Modulation of motion signals across the visual cortical hierarchy during bistable perception - Kim Beneyton; Heilbron, Micha; Kennedy, Henry; Knoblauch, Kenneth; De Lange, Floris (bioRxiv, 2023)
Top-down influences play a critical role in perception. In vision, an ideal paradigm for studying these influences exploits ambiguous sensory experience where perceptual interpretation fluctuates spontaneously over time. This allows addressing how the neural mechanisms of bottom-up and top-down signals interact during the construction of an internal representation of the outside world. An ambiguous visual experience reflects internally-driven representations varying over time and their resolution engages perceptual decision-making. With functional imaging, we investigated in human subjects how ambiguous perceptual states are represented within early visual areas using a bistable moving plaid that is alternatively perceived as two superimposed grating components sliding over each other obliquely or as a single rightward moving pattern. We show that direction-specific voxels encoding the current perceptual state are found across the entire cortical visual hierarchy, but unexpectedly that pattern selectivity is particularly strong in area V1. While oblique-tuned V1 voxels preferentially respond during the component percept, rightward-tuned voxels were selectively activated during the pattern perceptual state. Consideration of the intrinsic connectivity of area V1 suggests that complex pattern-selective activity at the lowest hierarchical level of visual cortex reflects feedback signals from higher-level areas. These findings address functional cortical hierarchy and the role of feedback signals on cortical processing underlying perception.Competing Interest StatementThe authors have declared no competing interest.Footnotes* https://data.ru.nl/collections/di/dccn/DSC_3018058.02_227?1